An Improved LMS Prefilter-Based PLL With Adaptive Controlling Parameter for Grid Synchronization and Islanded Operation of Batteryless Solar PV System - Modi, Gaurav; Singh, Bhim (IEEE transactions on industrial informatics, 2024)
In this article, we present a modified least mean square (M-LMS) adaptive filter-based controlled grid-integrated photovoltaic system (GPVS) with the capability for islanded operation during power cuts. The system employs a two-stage configuration to regulate the voltage at dc link. Designed M-LMS is utilized to extract ripple-free dq -axis components of grid voltages and load currents. These dq components of voltages are then processed through a phase-locked loop (PLL) to obtain angle and frequency information. Meanwhile, the dq -axis components of load currents contribute to integrate load compensation features within GPVS. Additionally, these components play a crucial role in decision-making processes for load shedding or automatic load control during islanded operation. In comparison to other algorithms, the M-LMS algorithm distinguishes itself by eliminating the need for a transformation matrix and uses angle as feedback instead of frequency to make the structure adaptive. It serves as a modified alternative to LMS, showcasing superior response compared to both LMS and second-order generalized integrator algorithms. Furthermore, the PLL structure is redesigned to address frequency variations resulting from phase changes during synchronization, contributing to achieving a seamless connection. To validate the designed control performance, simulations are conducted, and the system's effectiveness is verified through application on a test bench setup of the GPVS.